Some Theoritical Considerations Of English Language Teaching Curriculum Development - Sahuddin Sahuddin (Jurnal Ilmiah Profesi Pendidikan, 2019)
Teaching language in classroom at all levels in ELT curriculum sets up the main goal to learn and to teach language as to achieve discourse competence oral or written. Discourse means texts whether transactional or inter-personal written or oral. This means that students can do many types of action using language in a specific context such as in classroom, but this does not mean that they are not being taught other things out side of the classroom environment around them. The supporting competencies (linguistic, socio-culture) can include many themes and topics as presented in each subcomponents in competency. There are four steps of language learning can be applied and planned by teachers before teaching. Building knowledge of the field: guiding students to understand/elicit the main principles of the materials. Example, writing simple transactional conversation text. Modeling of the text: teachers give model of what they are doing. Teachers present an example of the transactional conversation text. Joint construction: collaborate with students while they are doing the simple conversational transactional text. Independent construction: let them do the simple conversational transactional text independently.